Improvement on yield of onion (Allium cepa L.) using different rates of organic manure and sowing seasons in South Eastern Nigeria - Patience Ukamaka Ishieze; Felicity Chidiebere Onah; Nathaniel Dauda (Jurnal Ilmu Pertanian, 2022)
This study aimed at determining how different rates of poultry manure affected the growth and production of onions (Allium cepa L.) in wet and dry seasons. The experiment was conducted from July to October 2019 and from January to April 2020 at the Department of Crop Science teaching and research farm, University of Nigeria Nsukka, South Eastern Nigeria. The experiment applied a randomized complete block design with nine replications spread over three blocks. The treatments were four doses of poultry manure (0, 10, 20 and 30 t.ha-1) tried in two seasons (wet and dry season). Prior to the investigations, soil analysis of the experimental site and poultry manure nutrient content were carried out. The growth pattern and yield was higher during the wet season. Poultry manure at amount of 30 t.ha-1 gave the best growth attributes (number of leaves, leaf length, and leaf diameter) 14.22, 53.67 cm and 0.88 cm respectively while the 20 t.ha-1 had the highest plant height and bulb fresh weight, 60.86 cm and 2 kg/plant respectively. The trend was not the same as in dry season planting because 20 t.ha-1 poultry manure differs significantly from other rates of poultry manure considered. Plant height, leaf length, leaf diameter and bulb fresh weight (57.64 cm, 55.28 cm, 0.84 cm and 0.63 kg/plant respectively) were statistically significantly (p < 0.05) different at 5% probability level.  Utilization of 20 t.ha-1 of poultry manure and planting in wet season gave the best growth and yield of onion vegetable.